Using phenolphthalein as a promising indicator to monitor the vacuum freeze-drying process - Liu, Lin; Wang, Ya; Fan, Daidi; Mi, Yu (Materials letters, 2015)
To improve the quality of the product, an important subject in vacuum freeze-drying process is to accurately monitor the state of water at its freezing stage and that of the residual water at its drying stage. In this paper, an easy-to-perform method is shown to monitor the state of water during the whole freeze-drying process (i.e. the state of water in the freezing stage and that of the residual water in drying stage) based on colour changes of phenolphthalein. A sample prepared with phenolphthalein was sensitive to structural changes of water hydrogen bonding network and exhibited colour-changing effect. This makes it possible to accurately trace the dynamic freeze-drying process, thus providing a valuable tool for preparing high-quality products.